Petroleum production handbook - Frick, Thomas C. (New York: McGraw-Hill, 1962)
The book examines reservoir engineering with graphic details and tables.
Includes index
Includes bibliographies.
usc 22/01/2019
Loans
Keywords: Petroleum engineering; Petroleum; Petroleum production